Serum laminin in malaria. Issue 9 (September 1994) - Wenisch, C; Graninger, W; Viravan, C; Looareesuwan, S; Parschalk, B; Wernsdorfer, W
Abstract : AIM–To determine serum laminin concentrations in patients with uncomplicated Plasmodium falciparum malaria. METHODS–An enzyme linked immunosorbent assay (ELISA) was used to determine serum laminin concentrations in 54 patients with acute uncomplicated P falciparum malaria during and after treatment, and in 17 control subjects in Bangkok, Thailand. RESULTS–Raised concentrations of soluble laminin were observed in patients (mean (SD) concentration 628 (225) ng/ml), compared with normal controls (490 (116) ng/ml), during the acute phase of the disease. During treatment, serum laminin concentrations decreased and returned to normal within three days. Serum laminin concentrations were correlated with parasite counts before treatment, and with the serum concentration of soluble intercellular adhesion molecule-1 (ICAM-1), soluble E-selectin, and soluble tumour necrosis factor receptor at 55 kilodaltons. CONCLUSIONS–These findings are compatible with an increased production or release of laminin in P falciparum malaria, which could indicate a role for the subendothelial basement membrane in the pathogenesis of the disease.